ENHANCING INDONESIA'S NATIONAL DEFENSE: SOLDIER SUPERVISION AND DISCIPLINE IN THE INDONESIAN NATIONAL ARMY - Pandjaitan, Manahan Budiarto; Khusaini, Mohamad (Jurnal Pertahanan dan Bela Negara, 2023)
The Indonesian National Military, as the main component of defense, together with all components of the nation and society, should foster National Resilience. Supervision and discipline are essential in supporting TNI work's professionalism to maintain the Unitary State of the Republic of Indonesia's national defense effort. The purpose of the study is to determine the ideal supervision mechanism in an institution to achieve the best performance of soldiers for strong National Resilience, analyze the disciplinary attitude of soldiers in improving the performance of TNI institutions as the main component of national defense for resilient National Resilience, and analyze the relationship between supervision and individual discipline related to achieving the best performance of soldiers on the performance of TNI institutions as the main component of national defense for resilient National Resilience. The research method uses a literature study approach with five stages: identification of research objectives, collection of literature sources, selection of literature sources, analysis and synthesis, and writing of articles. The result of the research is an ideal supervision mechanism in an institution, namely with a system that is careful, transparent, and oriented to soldiers' performance. The disciplinary attitude of soldiers affects a national defense system that is resilient, responsive, and able to face various threats because the disciplinary attitude of soldiers is implemented through rules that are well adhered to, able to complete tasks on time, have integrity, and a disciplinary attitude has a positive impact on the professionalism of soldiers. With a strong relationship between supervision and individual discipline, TNI can create an environment where soldiers can perform best, contributing significantly to solid and effective national resilience. Through strict supervision, soldiers will feel monitored and supervised in their every action, naturally encouraging a higher level of discipline.